2011
DOI: 10.1016/j.jeconom.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Panels with non-stationary multifactor error structures

Abstract: a b s t r a c tThe presence of cross-sectionally correlated error terms invalidates much inferential theory of panel data models. Recently, work by Pesaran (2006) has suggested a method which makes use of crosssectional averages to provide valid inference in the case of stationary panel regressions with a multifactor error structure. This paper extends this work and examines the important case where the unobservable common factors follow unit root processes. The extension to I(1) processes is remarkable on two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
492
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 790 publications
(506 citation statements)
references
References 26 publications
12
492
2
Order By: Relevance
“…Kapetanios et al (2011) show that these asymptotic results continu to hold in non-stationary panels provided that the idiosyncratic error term ε it is stationary. We outline our approach for testing whether this assumption (of cointegration) is satisfied in Section 4.3 below.…”
Section: Ccep Estimator For Model With Time-invariant Factor Loadingsmentioning
confidence: 76%
See 2 more Smart Citations
“…Kapetanios et al (2011) show that these asymptotic results continu to hold in non-stationary panels provided that the idiosyncratic error term ε it is stationary. We outline our approach for testing whether this assumption (of cointegration) is satisfied in Section 4.3 below.…”
Section: Ccep Estimator For Model With Time-invariant Factor Loadingsmentioning
confidence: 76%
“…More specifically, we use the Common Correlated Effects Pooled (CCEP) estimator of Pesaran (2006), which controls for unobserved common factors by adding cross-sectional averages of the data. As shown by Kapetanios et al (2011) this approach is also valid in a non-stationary panel context. A second contribution of this paper is that we allow and model time-variation in the access of countries to worldwide technology.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…(A.8) in the Appendix). Kapetanios et al (2011) have recently shown that the CCE estimator is consistent regardless of whether the common factors are stationary or nonstationary.…”
Section: Robustness Checksmentioning
confidence: 99%
“…can be either stationary or nonstationary, which does not influence the validity of the estimation (Kapetanios, 2011). In addition, the cross-sectional specific errors are permissible to be serially correlated over time and weakly dependent across the countries (Cavalcanti et al 2011).…”
mentioning
confidence: 99%